2002
DOI: 10.1046/j.1365-2249.2002.01875.x
|View full text |Cite
|
Sign up to set email alerts
|

Preventive effect of sulphated colominic acid on P-selectin-dependent infiltration of macrophages in experimentally induced crescentic glomerulonephritis

Abstract: SUMMARY Leucocytes infiltrate into renal tissue and are involved in the pathogenesis of crescentic glomerulonephritis. The initial event in the process of leucocyte infiltration is characterized by selectin‐mediated leucocyte rolling on endothelial surface. Role of selectins in pathogenesis of glomerulonephritis has still been controversial. Sulphated glycolipids and sulphated polysaccharides interfere with the binding of P‐ and L‐selectin with carbohydrate ligands on endothelial cells or on leucocytes. Here w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
25
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(28 citation statements)
references
References 45 publications
3
25
0
Order By: Relevance
“…Both of these adhesion molecules are upregulated in glomeruli of animals with crescentic anti-GBM GN and mediate glomerular infiltration of leukocytes (25,34 -36). Inhibition of P-selectin in anti-GBM GN prevents the development of disease by reducing glomerular T cell and/or macrophage recruitment (25,36), and attenuated renal injury in ICAM-1Ϫ/Ϫ mice is associated with reduced glomerular leukocyte infiltration (34). Previous reports have demonstrated that enhanced T cell influx into inflamed tissue (psoriatic skin lesions) as a result of CD80/86 co-stimulation can be associated with increased endothelial expression of P-selectin and ICAM-1 (37).…”
Section: Discussionmentioning
confidence: 99%
“…Both of these adhesion molecules are upregulated in glomeruli of animals with crescentic anti-GBM GN and mediate glomerular infiltration of leukocytes (25,34 -36). Inhibition of P-selectin in anti-GBM GN prevents the development of disease by reducing glomerular T cell and/or macrophage recruitment (25,36), and attenuated renal injury in ICAM-1Ϫ/Ϫ mice is associated with reduced glomerular leukocyte infiltration (34). Previous reports have demonstrated that enhanced T cell influx into inflamed tissue (psoriatic skin lesions) as a result of CD80/86 co-stimulation can be associated with increased endothelial expression of P-selectin and ICAM-1 (37).…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that several biological activities of SCA also require the sulfate group. 2,[6][7][8] Thus, the sulfation appears to be in general essential for exhibition or intensification of the biological activities of polysaccharides. In contrast, the present data showed that the inhibitory effect of CA on vascular smooth muscle cell proliferation is unaffected by the sulfation, suggesting that the polysaccharide chain structure of CA interacts for itself with the cells and the sulfate group does not influence the interaction.…”
Section: Discussionmentioning
confidence: 99%
“…2) have several biological activities including antiviral activities, [3][4][5] inhibition of the cytotoxic action of bee and snake venom, 6) inhibition of P-selectin-dependent macrophage infiltration in the glomeruli in experimental rat crescentic glomerulonephritis 7) and inhibition of fertilization of mouse gametes. …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…1B), originally isolated from Escherichia coli K1. 21) Although little is known about the biological activity of CA, O-sulfated CA (SCA), prepared by chemical sulfation of the CA chain, 22) exhibits several biological activities, including antiviral activities, [23][24][25] inhibition of the cytotoxic action of bee and snake venom, 26) inhibition of Pselectin-dependent macrophage infiltration in the glomeruli in experimental rats with crescentic glomerulonephritis, 27) and inhibition of the fertilization of mouse gametes. 28) However, the effects of CA and SCA on the vascular cell functions as well as the blood coagulation-fibrinolytic system have not been investigated.…”
Section: Introductionmentioning
confidence: 99%